Training academic staff for effective feedback in workplace-based assessment: a study in Bhutan - Sontosh Mukhia; Karma Tenzin (BMC Medical Education)
Abstract Introduction The feedback plays a critical role in competency-based education in both undergraduate and Postgraduate medical education. The study explores the impact of a faculty development program on feedback practices of residents and faculty of ENT and ER medicine at Gyalpo University of Medical Sciences of Bhutan (KGUMSB). Methods This mixed method study was conducted in two departments with 14 faculty members participating in the study. The questionnaire was used to obtain the perception of feedback before and after a Faculty Development Training (FDT) on good feedback practices. Student “t” test was used to compare the feedback perception at day 0 and 6 months and the responses were qualitatively analyzed using thematic analysis. Results (a) Quantitative: The confidence of faculty to provide feedback improved significantly after FDT as compared to before FDT and it persisted in the same for 6 months (p-value 0.041 and p-value 0.027 respectively). The overall perception of feedback as a tool significantly changed positively after FDT and at 6 months (p-value p-value = 0.000). (b) Qualitative: Two thematic areas of process and teaching-learning were analyzed. Faculty showed improved and more focused feedback after training, but signs of decline by 6 months highlighted the need for refresher training. Feedback initially improved for residents, as it became more constructive and useful, though by 6 months, it showed potential for further refinement and consistency. 55 -Conclusions The findings from this study are suggestive that feedback may have excellent potential as a tool for enhanced student learning in WPBA encounters.